The XXL Survey – XLVIII. X-ray follow-up of distant XXL clusters: masses, scaling relations, and AGN contamination†. Issue 2 (9th March 2022) - Duffy, R T; Logan, C H A; Maughan, B J; Eckert, D; Birkinshaw, M; Clerc, N; Ettori, S; Gastaldello, F; Koulouridis, E; Pierre, M; Ricci, M; Sereno, M; et al.
ABSTRACT: We use deep follow-up XMM–Newton observations of six clusters discovered in the XXL Survey at z > 1 to gain robust measurements of their X-ray properties and to investigate the extent to which scaling relations at low redshift are valid at z > 1. This sample is unique as it has been investigated for active galactic nucleus (AGN) contamination, which ensures measurements are not undermined by systematic uncertainties, and pushes to lower mass at higher redshift than is usually possible, for example with Sunyaev–Zel'dovich (SZ) selected clusters. We determine the flux contribution of point sources to the XXL cluster flux in order to test for the presence of AGN in other high-redshift cluster candidates, and find 3XLSS J231626.8−533822 to be a point source misclassified as a cluster and 3XLSS J232737.3−541618 to be a genuine cluster. We present the first attempt to measure the hydrostatic masses in a bright subsample of z > 1 X-ray selected galaxy clusters with a known selection function. Periods of high particle background significantly reduced the effective exposure times of observations (losing >50 per cent in some cases) limiting the power of this study. When combined with complementary SZ selected cluster samples at higher masses, the data appear broadly consistent with the self-similar evolution of the low redshift scaling relations between intracluster medium properties and cluster mass, suggesting that properties such as the X-ray temperature, gas mass, and SZ signal remain reliable mass proxies even at high redshift.